2021
DOI: 10.21831/cp.v40i2.35588
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Academic Achievement: Do Intellectual Humility and Emotional Intelligence Matter?

Abstract: Since emotional intelligence receives much attention in the context of academic success and intellectual humility is frequently studied in the context of career path, research concerning the relationship between emotional intelligence and intellectual humility on academic achievement is a necessity. This study aims to investigate that relationship while contributing to higher education on the insight to an employable graduate. The quantitative approach was implemented as the research framework by applying inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
1
0
2
Order By: Relevance
“…In addition, this research found that Islamic Education course has the potential to develop students' abilities from various aspects, including developing the cognitive side of learners through BBQ and BI activities. This fi nding reinforces the conclusion of Zamnah, which states that technology is an essential factor in fl oating one's cognitive abilities (Zamnah, 2017), emotional intelligence (Ratu, Rai, & Savitri et al, 2021)research concerning the relationship between emotional intelligence and intellectual humility on academic achievement is a necessity. This study aims to investigate that relationship while contributing to higher education on the insight to an employable graduate.…”
Section: Finding and Discussionsupporting
confidence: 83%
“…In addition, this research found that Islamic Education course has the potential to develop students' abilities from various aspects, including developing the cognitive side of learners through BBQ and BI activities. This fi nding reinforces the conclusion of Zamnah, which states that technology is an essential factor in fl oating one's cognitive abilities (Zamnah, 2017), emotional intelligence (Ratu, Rai, & Savitri et al, 2021)research concerning the relationship between emotional intelligence and intellectual humility on academic achievement is a necessity. This study aims to investigate that relationship while contributing to higher education on the insight to an employable graduate.…”
Section: Finding and Discussionsupporting
confidence: 83%
“…Aspek emosi peserta didik sebagai faktor yang dapat mempengaruhi keberhasilan belajar dan pengembangan diri. Berdasarkan penelitian ditemukan bahwa kecerdasan emosional sebagai salah satu pengaruh signifikan dalam mencapai proses pembelajaran dikarenakan dapat mempengaruhi intelektual individu dalam merencanakan, beradaptasi dan berinteraksi dalam konteks sosial dengan teman sebaya (Ratu, Rai, & Savitri, 2021). Demikian perkembangan emosi yang optimal perlu diperhatikan karena sebagai faktor pendukung keberhasilan belajar anak (Cyntia, Apriliya & Respati, 2022).…”
Section: Pendahuluanunclassified
“…Intellectual flexibility/humility as well as fluid intelligence are one of the most important cognitive predictors of academic success. Intellectual humility determines the efficiency of fulfilling tasks of different complexity degrees and efficiency of coping with problems in future life (Ratu, Rai and Savitri, 2021). Flexible intelligence (including non-verbal one) has an impact on creation in case of indirect influence of field independence (acting as cognitive style), which can determine academic success (Bouchefra et al, 2022;Giancola, Palmiero and D'Amico, 2022).…”
Section: Mental Representations As the Students' Academic Success Pre...mentioning
confidence: 99%